Modulated predictive control for indirect matrix converter - Tarisciotti, Luca; Lei, Jiaxing; Formentini, Andrea; Trentin, Andrew; Zanchetta, Pericle; Wheeler, Patrick; Rivera, Marco (IEEE, 2018)
Finite State Model Predictive Control (MPC) has been recently applied to several converter topologies as it can provide many advantages over other MPC techniques. The advantages of MPC include fast dynamics, multi-target control capability and relatively easy implementation on digital control platforms. However, its inherent variable switching frequency and lower steady state waveform quality, with respect to standard control which includes an appropriate modulation technique, represent a limitation to its applicability. Modulated Model Predictive Control (M2PC) combines all the advantages of MPC with the fixed switching frequency characteristic of PWM algorithms. The work presented in this paper focuses on the Indirect Matrix Converter (IMC), where the tight coupling between rectifier stage and inverter stage has to be taken into account in the M2PC design. This paper proposes an M2PC solution, suitable for IMC, with a switching pattern which emulates the desired waveform quality features of Space Vector Modulation (SVM) for matrix converters. The switching sequences of the rectifier stage and inverter stage are rearranged in order to always achieve zero-current switching on the rectifier stage, thus simplifying the current commutation strategy.